Lansoprazole and carbonic anhydrase IX inhibitors sinergize against human melanoma cells. (1st November 2016) - Federici, Cristina; Lugini, Luana; Marino, Maria Lucia; Carta, Fabrizio; Iessi, Elisabetta; Azzarito, Tommaso; Supuran, Claudiu T.; Fais, Stefano
Abstract: Context : Proton Pump Inhibitors (PPIs) reduce tumor acidity and therefore resistance of tumors to drugs. Carbonic Anhydrase IX (CA IX) inhibitors have proven to be effective against tumors, while tumor acidity might impair their full effectiveness. Objective : To analyze the effect of PPI/CA IX inhibitors combined treatment against human melanoma cells. Methods : The combination of Lansoprazole (LAN) and CA IX inhibitors (FC9-399A and S4) has been investigated in terms of cell proliferation inhibition and cell death in human melanoma cells. Results : The combination of these inhibitors was more effective than the single treatments in both inhibiting cell proliferation and in inducing cell death in human melanoma cells. Discussion : These results represent the first successful attempt in combining two different proton exchanger inhibitors. Conclusion : This is the first evidence on the effectiveness of a new approach against tumors based on the combination of PPI and CA IX inhibitors, thus providing an alternative strategy against tumors.